Lärares självförtroende i bedömarrollen och dess inverkan på samstämmighet i betygsättning - Johannisson,Anna; Svensson,Karin (2013)
This study focuses on 6th grade Swedish teachers’ self-efficacy in the grading procedure, hypothesizing that high versus low self-efficacy will have an impact on the grade the teacher give an authentic short story. A total of 34 teachers answered the survey and the results showed that the teachers were inconclusive in their grading of the short story, and that self-efficacy and attitude towards the grading criteria material were positively correlated (r=0,37; p<0,05). Furthermore, no correlation was found between professional experience and self-efficacy. Finally, the analysis showed that teachers are inconclusive in their grading process, although the hypothesis suggesting that high- versus low teacher grading- efficacy would affect grading showed no result. These are interesting results encouraging further research in this area.
Keywords: Attityd; Självförtroende; Betygssystem; Betygsättning; Lärare